2022
DOI: 10.32394/rpzh.2022.0221
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity score and the incidence of chronic kidney disease in an agricultural Moroccan adults population

Abstract: Background. Healthy diet plays an important role in the management of chronic kidney disease (CKD) and in the prevention of related comorbidities. Dietary diversity score (DDS) is well recognized as an indicator for assessing diet quality and food security. However, its association with CKD has not been investigated. Objective. The aim of this study was to estimate the prevalence of CKD and to evaluate its association with DDS among a Moroccan adults from Sidi Bennour province. Materials and methods. A cross s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We also observed some variations in the association between different DDSs and possible sarcopenia, while the associations between DDS (total diet, animal-based diet, and plant-based diet) and possible sarcopenia were more pronounced. When constructing a DDS, the food groups included were different across studies and may contribute to the inconsistent findings, partly due to the study population and purpose ( 21 , 32 , 33 , 37 ). In the literature, the classification of DDS was based on the US Department of Agriculture (USDA) food guide pyramid (five food groups), the Chinese Dietary Guideline (10 food groups), and the Food and Agriculture Organization (FAO) guidelines (9 food groups) ( 32 , 34 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also observed some variations in the association between different DDSs and possible sarcopenia, while the associations between DDS (total diet, animal-based diet, and plant-based diet) and possible sarcopenia were more pronounced. When constructing a DDS, the food groups included were different across studies and may contribute to the inconsistent findings, partly due to the study population and purpose ( 21 , 32 , 33 , 37 ). In the literature, the classification of DDS was based on the US Department of Agriculture (USDA) food guide pyramid (five food groups), the Chinese Dietary Guideline (10 food groups), and the Food and Agriculture Organization (FAO) guidelines (9 food groups) ( 32 , 34 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES) concluded that DDS could be viewed as a convenient and fast indicator for assessing dietary diversity and observed that improved diet quality was associated with increased dietary diversity ( 19 , 22 ). Previous studies have additionally demonstrated an association between DDS and chronic diseases, such as cardiovascular diseases, cancer, diabetes, and metabolic syndrome, as well as its correlation with improved health status and prolonged longevity ( 21 23 ). According to data from several investigations, higher DDS was also associated with better cognitive function, fewer physical limitations, and lower psychological stress in the elderly ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations